Breast Cancer, BRCA Mutations, and Attitudes Regarding Pregnancy and Preimplantation Genetic Diagnosis. (20th June 2014) - Woodson, Ashley H.; Muse, Kimberly I.; Lin, Heather; Jackson, Michelle; Mattair, Danielle N.; Schover, Leslie; Woodard, Terri; McKenzie, Laurie; Theriault, Richard L.; Hortobágyi, Gabriel N.; Arun, Banu; Peterson, Susan K.; et al.
Abstract: Background: Women with premenopausal breast cancer may face treatment-related infertility and have a higher likelihood of a BRCA mutation, which may affect their attitudes toward future childbearing. Methods: Premenopausal women were invited to participate in a questionnaire study administered before and after BRCA genetic testing. We used the Impact of Event Scale (IES) to evaluate the pre- and post-testing impact of cancer or carrying a BRCA mutation on attitudes toward future childbearing. The likelihood of pursuing prenatal diagnosis (PND) or preimplantation genetic diagnosis (PGD) was also assessed in this setting. Univariate analyses determined factors contributing to attitudes toward future childbearing and likelihood of PND or PGD. Results: One hundred forty-eight pretesting and 114 post-testing questionnaires were completed. Women with a personal history of breast cancer had less change in IES than those with no history of breast cancer ( p = .003). The 18 BRCA-positive women had a greater change in IES than the BRCA-negative women ( p = .005). After testing, 31% and 24% of women would use PND and PGD, respectively. BRCA results did not significantly affect attitudes toward PND/PGD. Conclusion: BRCA results and history of breast cancer affect the psychological impact on future childbearing. Intentions to undergo PND or PGD do not appear to change after disclosure of BRCA results. Additional counseling for patients who have undergone BRCA testing may be warranted to educate patients about available fertility preservation options. Abstract : The purpose of this study was to evaluate how BRCA genetic test result disclosure and patient characteristics influence attitudes about preimplantation genetic diagnosis (PGD), prenatal diagnosis (PND), and future childbearing. Intentions to undergo PND or PGD do not appear to change after disclosure of BRCA results. Additional counseling for patients who have undergone BRCA testing may be warranted to educate patients about available fertility preservation options.